Efficacy of entomopathogenic fungi for control of walnut blue butterfly (Chaetoprocta odata [Hewitson, 1865]) in walnut (Juglans regia L.) under laboratory conditions - Shazia GULL; Ajaz RASOOL; Tariq AHMAD (Acta Agriculturae Slovenica)
Biological control nowadays is rapidly growing to reduce the incessant use of chemical insecticides for control of various insect pests. In the present study, entomopathogenic fungi are used to determine insecticidal activity against walnut blue butterfly under laboratory conditions. The experimental setup was completely randomized design (CRD) with two treatments along with control with different concentrations of entomopathogenic fungi. The bioassay was carried out by spraying second larval instar of Chaetoprocta odata [Hewitson 1865] with 1, 2, 3 & 4 % conidial concentration of Beauveria bassiana (Balsamo) Vuill. (1912) and Isaria fumosorosea Wize (1904). The results of this study showed that all the concentrations showed remarkable pathogenic activity but I.  fumosorosea was highly pathogenic and recorded the highest mortality rate of 93.33 % after 144 hours compared to B. bassiana where 73.33 % mortality was reported. LC50 values for B. bassiana (4.15) was higher than that of I. fumosorosea (3.34) which indicates that I.  fumosorosea was more effective against C. odata population. Among different concentrations of I. fumosorosea, 4 % concentration was the most effective with lowest LC50 values.